On the collection of MiFIR transparency data: An application to the ECB eligible marketable assets - Gonzalo Camba-Méndez; Jan Jerzy Darecki; Andrés Manzanares; Matteo Metra; Riccardo Vergnano (European Central Bank (ECB), 2025)
One of the main goals of launching the EU's second Markets in Financial Instruments Directive (MiFID II) and the respective Markets in Financial Instruments Regulation (MiFIR) was to increase the transparency of transactions in financial markets. Prior to MiFID II, transparency requirements in financial markets were limited mostly to equities traded in regulated markets. Following MiFID II, transactions now need to be publicly reported for a broader range of financial assets. Furthermore, disclosures on financial transactions are not restricted to those transactions executed in regulated markets but apply also to those executed over the counter. Importantly, this information should be made available free of charge, ensuring non-discriminatory access, within the 15 minutes following the transaction. The published information should also be machine-readable. The purpose of this paper is to show how a relatively simple IT tool may be devised that gathers data on market prices and transacted volumes published in compliance with MiFID II. We steer our simple IT tool towards retrieving data on those financial assets that are eligible for use as collateral in Eurosystem credit operations. This includes those assets eligible for outright purchase under the various monetary policy programmes launched by the Eurosystem. In view of the importance of UK financial markets when it comes to trading in Eurosystem eligible marketable assets, our tool also covers transactions and quotes reported by UK trading venues and investment firms in compliance with UK MiFIR. Apart from the merits and potential of our IT tool, this paper documents some of the tool's shortcomings related to processing the posted MiFID II and UK MiFIR raw data. It also covers some of the deficiencies associated with the data. Increased market transparency contributes to deeper and more integrated financial markets, potentially supporting economic growth. ECB access to these rich financial market data is very important for the conduct of its monetary policy. This is the case not only from the perspective of gathering all information relevant for monitoring financing conditions in euro area financial markets. It is also the case that the availability of pre-trade and post-trade data published in compliance with MiFIR could be a useful day-to-day tool for central bank monetary implementation and risk mitigation. The data collected provide a rich description of the price, liquidity and depth of various types of ECB eligible marketable assets.
Keywords: C81; D40; G10; 330; MiFID II; financial market prices; ECB eligible assets